Phomopsis azadirachtae a New Destructive Causative Agent of Neem Dieback and its Management through Fungicides and Endophytes - Kirtika, Thaduri; Basha, S. Ameer; Ramya, V.; Ramanjaneyulu, A. V. (International Journal of Economic Plants, 2025)
The present study was conducted during rabi (October–May, 2023–24) at the Department of Plant Pathology and Central Instrumentation Cell, College of Agriculture, Professor Jayashankar Telangana Agricultural University, Rajendranagar, Hyderabad, Telangana, India to report Phomopsis azadirachtae a new destructive causative agent of neem dieback and its management through fungicides and endophytes. Die-back of neem disease is presently a major devastating disease in India, resulting in almost 100% loss of fruit production and drastic reduction in evergreen canopy. Seven isolates of Phomopsis azadirachtae infecting neem collected from different districts of Telangana and identified based on morphological and cultural characteristics and molecular studies were carried out. They varied significantly in colony colour, growth pattern on Potato Dextrose Agar medium and isolates identified by molecular method, using ITS (ITS1 and ITS4) sequencing. Fifteen endophytic fungi and eight endophytic bacteria were isolated from neem leaves. Further, Bioefficacy of Endophytes was carried out against die back pathogen (Phomopsis azadirachtae). The potential endophytes were identified by ITS sequencing Six systemic fungicides Carbendazim, Hexaconazole, Thiophanate methyl, Tricyclazole, Isoprothiolane, Metalaxyl was evaluated against Phomopsis azadirachtae with different concentrations 10 ppm, 100 ppm 250 ppm, 500 ppm, 1000 ppm. Carbendazim and Thiophante methyl both were significantly inhibiting the growth of pathogen. Effect of potential endophytes and their combinations on plant growth promotion followed by roll paper towel method. In vivo studies evaluating potential endophytes and their combinations against neem die-back pathogen was carreid out inoculated on 2–3 months seedlings showing the disease incidence. Development of effective, eco-friendly management strategies is most important.